THE EFFECT OF PRODUCT KNOWLEDGE AND SOCIAL MEDIA MARKETING ON THE BRAND SWITCHING OF FAST MOVING CONSUMERS GOODS PRODUCTS DURING THE COVID 19 PANDEMIC - R.A. Aisah Asnawi; Etvin Rizal Tamher; Merry Pelupessy (Manis: Jurnal Manajemen dan Bisnis, 2021)
This research aims to determine the effect of product knowledge and social media marketing on the brand switching of fast moving consumers goods (FMCG) products during the COVID-19 pandemic. The type of research is quantitative with the use of regression analysis techniques and SPSS analysis tools version 23. The number of respondents in this research are 100 FMCG users spread across five villages in Central Maluku Regency. Based on the research results, social media marketing has a negative effect on brand shifting, this is due to the more information received, the more selective consumers tend to be. The era of the internet today makes consumers more critical and think about the validity of information, especially related to health. Meanwhile, product knowledge is just the opposite. Product knowledge has a positive effect on brand switching. This is simply because product knowledge is more relevant and becomes a reference for shifting health product brands. People are increasingly educated and trusting brands that have a good reputation. A well-known brand is easy to gain the trust of the public or respondents.